Off-Grid System Development for House Car Pouch Lighting - Ranjit, S.S.S.; Anas, S.A.; Tan, CheeFai (2011)
Practically to electrify lighting system electricity supply is a necessity to power the light. Thus, solar energy is known as an alternative source to provide electricity. This paper presents an off-grid system development for house car porch lighting system. Development of the system is composed of photovoltaic panel, environmental sensors, charge controller, battery and lighting loads such as florescent lamp. The off-grid system focuses to supply electricity in small scale which is integrated with some energy saving characteristics. An auto timer and smart charge controller is integrated into the off-grid system to turn-on and turn-off the lighting at the house car pouch. Integration of some smart functions is an ideal solution for small scale electricity supply or particularly for location which cannot be accessed by grid supply.